2020
DOI: 10.1016/j.amjsurg.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the affordable care act (ACA) Medicaid Expansion on access to minimally invasive surgical care

Abstract: INTRODUCTION-This study aims to evaluate the effect of the ACA Medicaid expansion on the utilization of minimally invasive (MIS) approaches to common general surgical procedures. METHODS-Wequeried five Healthcare Cost and Utilization Project State Inpatient Databases to evaluate rates of utilization and costs of MIS and open approaches pre and post Medicaid expansion.RESULTS-117,241 patients met the inclusion criteria. Following the enactment of the ACA, use of both laparoscopic gastric bypass (IRR 1.08; 95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Previous studies on the impact of the ACA expansion on cancer surgery have demonstrated increased rates of surgical intervention in lung and colorectal populations following the ACA expansion. 12-14 Our study demonstrated increased utilization of MIS approaches in ACA expansion states, but not due to the ACA implementation per se. One potential reason for this difference is that these states had already worked to improve access to care in ways other than the ACA.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies on the impact of the ACA expansion on cancer surgery have demonstrated increased rates of surgical intervention in lung and colorectal populations following the ACA expansion. 12-14 Our study demonstrated increased utilization of MIS approaches in ACA expansion states, but not due to the ACA implementation per se. One potential reason for this difference is that these states had already worked to improve access to care in ways other than the ACA.…”
Section: Discussionmentioning
confidence: 58%
“…10 Nevertheless, some studies have reported fewer substantial changes in racial health disparities following the ACA, possibly due to regional variations in its implementation. 11,12 Furthermore, studies have concluded that potentially eligible Black and Hispanic patients were less likely to be referred to a bariatric surgeon. Additionally, these patients may be excluded from surgical evaluation for not meeting presurgical lifestyle modification requirements.…”
Section: Discussionmentioning
confidence: 99%
“…We observed an overall 17% increase in elective spine surgical volume, similar to rate changes found in studies that evaluated major general surgery procedures such as gastric bypass surgery (8%), paraesophageal hernia or reflux disease surgery (17%), cancer surgical procedures (12%), hernia repair (16%), and vascular surgery (20%). 8,[32][33][34] Although each of these conditions differs with regard to the urgency of treatment and the likely unmet demand among uninsured patients, the impact of Medicaid expansion was similar. These findings suggest that observed changes in procedural volume may partly reflect the degree to which surgeons balance new Medicaid demand with maintaining privately insured volumes, a tradeoff that appears to bear similarity across a variety of major health conditions.…”
Section: Discussionmentioning
confidence: 99%